2017
DOI: 10.1155/2017/1873209
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Ultrasound/MRI Fusion for Suprasacral Parallel Shift Approach to Lumbosacral Plexus Blockade and Analysis of Injectate Spread: An Exploratory Randomized Controlled Trial

Abstract: Fused real-time ultrasound and magnetic resonance imaging (MRI) may be used to improve the accuracy of advanced image guided procedures. However, its use in regional anesthesia is practically nonexistent. In this randomized controlled crossover trial, we aim to explore effectiveness, procedure-related outcomes, injectate spread analyzed by MRI, and safety of ultrasound/MRI fusion versus ultrasound guided Suprasacral Parallel Shift (SSPS) technique for lumbosacral plexus blockade. Twenty-six healthy subjects ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Strid et al used Dotarem to investigate local anesthetic spread and seemed to confirm diffusion of Dotarem through membranous fasciae, even into the epidural space. 17 Dotarem possesses an essentially neutral pH (6)(7)(8) in a water-based solution, therefore not interfering with ropivacaine's capability to diffuse through lipophile membranes. We are confident that this study adds substantial knowledge concerning the spread of local anesthetic solutions, be it by hydrostatic pressure or diffusion through extracellular space.…”
Section: Original Researchmentioning
confidence: 99%
“…Strid et al used Dotarem to investigate local anesthetic spread and seemed to confirm diffusion of Dotarem through membranous fasciae, even into the epidural space. 17 Dotarem possesses an essentially neutral pH (6)(7)(8) in a water-based solution, therefore not interfering with ropivacaine's capability to diffuse through lipophile membranes. We are confident that this study adds substantial knowledge concerning the spread of local anesthetic solutions, be it by hydrostatic pressure or diffusion through extracellular space.…”
Section: Original Researchmentioning
confidence: 99%
“…Ultrasound‐guided sacral plexus block can be used to provide anaesthesia and analgesia for hip surgery. Recently, three methods of ultrasound‐guided sacral plexus block have been reported: a short‐axis method ; long‐axis method ; and a suprasacral parallel shift approach to lumbosacral plexus blockade . These require the patients to be in either a lateral decubitus or a prone position, which can be difficult to achieve for hip trauma patients.…”
mentioning
confidence: 99%
“…The UCOT (image fusion) has been applied in the field of regional anesthesia. Strid et al 61 conducted the first randomized controlled trial of ultrasound/MRI fusion for lumbosacral plexus block and confirmed that ultrasound/MRI fusion technology was effective and safe. However, compared with ultrasonic guidance, it requires a longer preparation process.…”
Section: Ucot For Regional Anesthesiamentioning
confidence: 98%